Board composition, ESG practices, and firm performance: Evidence from the Pakistan stock exchange - Shah, Sayyed Sadaqat Hussain; Basit, Abdul; Ahmed, Sheraz; Khan, Muhammad Asif; Tangl, Anita (The Economics and Finance Letters, 2024)
This study delves into the intricate relationship between corporate governance factors, including board size and the proportion of non-executive directors, and firm performance, with a specialized focus on environmental, social, and governance (ESG) considerations. Employing a secondary data analysis methodology, the research draws insights from a comprehensive dataset comprising 100 companies listed on the Pakistan Stock Exchange over a period spanning from 2018 to 2022. The study investigates these relationships using rigorous regression analysis to uncover significant findings. The analysis reveals a robust positive correlation between larger board sizes and firm performance, indicating that companies with expanded boards tend to exhibit improved financial performance within the Pakistani market landscape. Conversely, a higher proportion of non-executive directors is associated with decreased performance, highlighting potential challenges stemming from board composition. Furthermore, the research unveils the pivotal role of ESG practices in augmenting the positive relationship between board size and firm performance. However, it notes that this enhancement weakens as the proportion of non-executive director’s increases, suggesting a nuanced interplay between corporate governance structures and ESG considerations. Practically, the study underscores the critical importance of fostering diverse and well-structured boards while integrating ESG principles into corporate governance frameworks. By carefully considering board composition and embracing ESG practices, organizations can not only enhance their financial performance but also promote sustainability and long-term value creation, aligning with evolving stakeholder expectations and regulatory requirements in the Pakistani business landscape.